Recycling agroâindustrial waste to produce amylase and characterizing amylaseâgold nanoparticle composite - Aditya Mojumdar; Jashmini Deka (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Amylase being one of the most important industrial enzymes requires large-scale production. When producing an enzyme, high productivity, high purity and low production costs need to be considered. This study focuses on comparing various agro-industrial waste substrates, for production of alpha-amylase using Bacillus amyloliquefaciens. Moreover, it studies the stability and activity of amylaseâgold nanoparticles composite. Method This study is divided into two parts, in the first part various agro-industrial waste substrates, such as wheat bran, rice bran and potato peel were used to produce alpha-amylase using solid-state fermentation (SSF). The production of the enzyme was quantified and compared in specific enzyme activity units. In the second part, change in the stability and activity of amylase in enzymeâgold nanoparticles (AuNPs) composite has been discussed. Results Highest enzyme production was observed in wheat bran and potato peel substrate with specific enzyme activity of almost 1.2 U/ug and 1.1 U/ug. Among combination substrates, wheat bran with potato peel showed a high enzyme production of 1.3 U/ug. On the other hand, the optimum temperature for amylase activity shifted to 55 °C in the composite compared to 37 °C for free enzyme. Conclusion Comparison of specific enzyme activity of extracts from various substrates showed that wheat bran alone, and in combination with potato peel, produces active and pure amylases. To stress on various catalytic activities of alpha amylase, the capability of the enzyme to synthesize gold nanoparticles and the effect of conjugation of the nanoparticle on its optimum catalytic activity are also discussed in this paper.